Successful outcome after surgical correction of large colon atresia in a colt foal. (6th October 2020) - Skov Hansen, S.; Mattei, C.; Treffenberg Pettersson, H.; Grabski, M.
Summary: This report describes successful surgical correction and long‐term survival of a case of large colon atresia in a 24‐h‐old Warmblood colt, referred with signs of unrelenting abdominal pain and a suspicion of meconium impaction. Radiographic and ultrasonographic examination was indicative of large colon meconium impaction with secondary ileus. Due to deterioration of the foal, surgery was recommended. An atretic segment was found between the left ventral and dorsal large (ascending) colon. A band of fibrous tissue with no identifiable lumen connected the segments. Surgical correction was done by performing a stapled side‐to‐side anastomosis. Twelve days after surgery, the foal was discharged. Twenty‐two months after discharge, the owner reported the foal developing as expected compared with its peers, but had a mild, self‐limiting episode of colic at 20 months of age.